Efektivitas Ekstrak Daun Matoa (Pometia pinnata) sebagai Antibakteri Staphylococcus epidermidis - Rossalinda Rossalinda; Fitria Wijayanti; Damayanti Iskandar (Stannum : Jurnal Sains dan Terapan Kimia, 2021)
A natural alternative that can be used to inhibit the growth of Staphylococcus epidermidis bacteria is matoa leaves (Pometia pinnata). Matoa leaves contain secondary metabolites such as flavonoids, tanins, and saponins which are known as an antibacterial. The purpose of this study was to determine the effectiveness of matoa leaves extract as an antibacterial agent for Staphylococcus epidermidis. This study used the disc diffusion method, using deodorant as a positive control, aquadest as a negative control and concentration variations matoa leaves extract of 15%, 20%, 25% and 30%. The matoa leaves were extracted using the maceration method with 96% ethanol. Antibacterial testing in this study was characterized by a clear zone or zone of inhibition around the disc paper. The results of the antibacterial test in this study have to different inhibition zones, that is a sample concentration of 15% the inhibition zone value is 0,125 mm. The sample concentration of 20% the inhibition zone is 3 mm. The sample concentration of 25% the inhibition zone is 2,312 mm and the sample concentrasion of 30% the inhibition zone is 0,875 mm. The extract of matoa leaves can be used as an antibacterial, because according to Pan Chen Wu Tang and zao (2009) the extract of matoa leaves could be applied as inhibitor of the growth of Staphylococcus epidermidis at a sample concentration of 20% is in the weak to moderate category